ANALISA PENGARUH VARIASI PUTARAN DAN FEED RATE PADA MESIN FRAIS TERHADAP KEKASARAN PERMUKAAN DAN LAJU KOROSI PADA BAJA KARBON SEDANG - Muhammad Jen Latuconsina; Nevada. J. M. Nanulaitta; Josef Matheus; Fredrick Demattacco (Journal Mechanical Engineering, 2024)
A milling machine or milling machine is a machine tool used in the manufacturing process to produce components or parts with the desired shape and size. Milling machines have an important role in the oil and gas industry, especially in the manufacture of components used in oil and gas industry equipment such as grooves on shafts and gears used in drilling equipment and oil and gas production are often made of medium carbon steel because of its strength and durability. This study aims to obtain roughness values and corrosion rates on medium carbon steel through the milling process with variations in rotation of 900 rpm and 1100 rpm and feed rates of 42 mm / min and 76 mm / min with dromus cooling media. The results of this study obtained the highest average roughness value at a rotation speed of 900 rpm and a feed rate of 42 mm/minute, which is 6.64 µm (Ra) and 31.1 µm (Rz), while the lowest average roughness value at a rotation speed of 1100 rpm and a feed rate of 42 mm/minute is 6.23 µm (Ra) and 30.8 µm (Rz), for a rotation speed of 1100 rpm and a feed rate of 76 mm/minute is 7.92 µm (Ra) and 37.1 µm (Rz). The higher the rotation speed and the lower the feed rate, the lower the roughness value, and vice versa. The highest corrosion rate is at 900 rpm and 76 mm/minute feed rate, which is 0.02194 (mm/y), while the lowest corrosion rate is at 1100 rpm and 42 mm/minute feed rate, which is 0.01555 (mm/y). The higher the surface roughness, the faster the corrosion rate, and vice versa. Keyword : milling machine, surface roughness, corrosion rate, medium carbon steel